Snippets of Ancient Indian Mathematics - Shailesh Shirali, (SCHOOL SCIENCE, 2025)
It is important that mathematics is taught with a sense of its history. It is not as though one needs to study the history of mathematics as a separate subject. Rather, it is appropriate to bring in problems and contexts from history into the study of mathematical topics wherever feasible and relevant. This can add immensely to the appreciation and enjoyment of the subject. This article is based on a talk given on 11 November, 2022 for the “Listening to Learn” Webinar series of the National Council Educational Research and Training (NCERT). In the talk, we dealt with four problems, each of which has a connection with some topic from ancient Indian mathematics: (a) Magic squares of orders 3 and 4; (b) The mathematics of compositions and prosody, and the Fibonacci numbers, also known as the Virahanka-Gopala-Hemachandra numbers; (c) Aryabhata’s kuttaka (‘pulverizer’) algorithm and the jugs-and-water-cups problem; (d) Brahmagupta triangles. The focus in each case was on the mathematics of the problem and not on the history; but we also touched upon the historical aspect. We have followed the same style in this article. There is great beauty and richness in studying such problems. It would have great value if high school mathematics were taught with glimpses of such gems